Monitoring mangrove crab Ucides cordatus Linnaeus, 1763 (Crustacea: Ucididae) landing in the Parnaíba River Delta: fishing characteristics, social and economic aspects. - FOGACA, F. H. dos S. (2018)
The century-old mangrove crab Ucides cordatus Linnaeus, 1763 harvesting is a traditional activity of Northeastern Brazilian coastal communities, who use it as food, source of income and cultural reference. The extractivism and marketing of this crustacean is essential for the socio-economic development of the states of Maranhão, Piauí and Ceará.